1998
DOI: 10.1016/s0735-1097(97)00506-8
|View full text |Cite
|
Sign up to set email alerts
|

Myonecrosis After Revascularization Procedures

Abstract: The detection of elevated cardiac enzyme levels and the occurrence of electrocardiographic (ECG) abnormalities after revascularization procedures have been the subject of recent controversy. This report represents an effort to achieve a consensus among a group of researchers with data on this subject. Creatine kinase (CK) or CK-MB isoenzyme (CK-MB) elevations occur in 5% to 30% of patients after a percutaneous intervention and commonly during coronary artery bypass graft surgery (CABG). Although Q wave formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
271
2
16

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 501 publications
(298 citation statements)
references
References 88 publications
9
271
2
16
Order By: Relevance
“…The rate of PCI-related MI in our patients (4.8%) was consistent with the rate reported in the literature (6,7). However, no abrupt vessel closure was observed in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The rate of PCI-related MI in our patients (4.8%) was consistent with the rate reported in the literature (6,7). However, no abrupt vessel closure was observed in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In only one patient, that value was exceeded, characterizing periprocedure infarction. The percentage of elevations in CK-MB activity in our study are lower than those reported in the literature, usually occurring in 15 to 25% of the patients 2,6,7 . This may be attributed to the exclusion of patients more prone to enzyme release (patients with lesions in the saphenous vein graft and those with recent acute coronary syndrome) 8,9 , and also to the influence of the technical characteristics and controlled invasiveness strategy that characterized our interventions (total time of balloon inflation < 120 seconds in 87% of the patients, maximum pressure of stent deployment ≤ 16 atmospheres in 70%, direct implantation of the prosthesis in 45% of the patients).…”
Section: Incidence Of Intracardiac Thrombus and Thromboembolism In Thcontrasting
confidence: 88%
“…
The systematic assessment of total creatine kinase (total CK) and its MB subfraction (CK-MB) after percutaneous coronary intervention shows that 5% to 40% of the patients successfully treated have an elevation in the serum level of those enzymes, which may represent a certain degree of myocardial necrosis [1][2][3] . Recently, the analysis of other very sensitive biochemical markers specific for identifying myocardial damage (CK-MB mass, troponins T and I) has intensified the detection of that phenomenon, which has been much more frequently observed with the implantation of coronary stents 4,5 .

This study aimed at establishing the clinical meaning of those alterations and their impact on the occurrence of adverse cardiac events.

…”
mentioning
confidence: 99%
“…CK-MB is a sensitive marker of myonecrosis and has been detected in 5%-50% of patients after PCI (Abdelmeguid and Topol, 1996;Califf et al, 1998;Kanaparti and Brown, 2000). The levels of serum CK-MB were significantly elevated after PCI, but values were still within the normal range, indicating that PCI induced a low-grade injury but not necrosis of the myocardium.…”
Section: Fig 4 Associations Between P-selectin (A)/mg (B) and Adversmentioning
confidence: 99%